ACQUISITION OF OWNERSHIP OVER THE PLEDGED THING BY THE CREDITOR IN ROMAN LAW (IMPETRATIO DOMINII) - Sič, Magdolna; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
It is less known that since the Severan Dynasty the creditor had the opportunity to ask the emperor for permanent ownership over the pledged thing (impetratio dominii). It is known, however, that the protection of the debtor’s interests, given that it was easier to collect taxes from them than from large land-owners, was of utmost importance for imperial finances. Therefore, apart from prohibiting the stipulation of lex commissoria, as well as conditioning pactum Marcianum with just price of the pledged thing, the rights of the debtor were protected by subjecting impetratio dominii to several conditions. Imperatio dominii depended on a publicly announced previous attempt of sale as well as on its annulment in case the creditor continues to collect interest after the acquisition of ownership over the pledged thing. Unsatisfied with the lack of application of these conditions in practice, Justinian posted additional conditions for the application of this institute in 530: the obligation to attempt to sell the pledged thing within two years; to inform the debtor about it even after the expiration of this deadline, in order to give him the opportunity to pay his debt; to seek special approval of the emperor for the acquisition of ownership after the expiration of these deadlines; by introducing a subsequent possibility for the debtor to repurchase the pledge from the creditor within two years; making irreversible the creditor’s ownership over the pledged thing only after the expiration of approximately four years; fair assessment of value of the pledged thing with the obligation of the creditor to return the surplus to the debtor as well as his right to request the payment of the outstanding amount from the debtor. This paper explores the emergence and evolution of imperatio dominii as well as the circumstances that lead to its emergence.